Yellow bristle grass seed killed in maize silage - Trolove, M.R.; Dowsett, C.A. (New Zealand Plant Protection, 2015)
Yellow bristle grass (Setaria pumila) is a serious weed that reduces dairy farm profitability and could potentially infest productive land throughout New Zealand Supplementary feed is used extensively in the dairy industry and farmers are concerned that yellow bristle grass seed may be spread with maize silage Previous studies showed that its seeds did not survive burial in covered silage stacks after 1 week To further investigate the decline in seed viability mesh bags containing 50 seeds were buried at 0 and/or 400 mm depth in two covered Waikato silage stacks and retrieved after 1 2 3 5 and 7 days Germination prior to seed burial was 69 and viability using tetrazolium staining was 88 Germination was reduced after 1 day to 1236 2 days to 030 3 days to 04 and 5 days to 0 Viability was reduced after 1 week from 50 to 40 Temperature and pH conditions during this study were not considered sufficient for rapid seed decay and therefore it appeared that chemicals released after ensiling were responsible Further investigation into mechanisms behind this rapid decay and its potential for effective weed seed control is warranted